Presentation, Treatment and Outcomes of Acute Coronary Syndrome in a Tertiary Care Hospital in Central Nepal - Barakoti, Murari Prasad; Regmi, S R; Dhital, B M (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Nepal is facing with increasing rate of coronary artery disease, yet little is known about presentation, treatment and outcome of this disease in our population and our setting. We aimed to document the characteristics in consecutive cases in a tertiary level hospital. MATERIAL AND METHODS: Seventy eight total cases were documented in six months period and evaluated the data on presentation, management, in-hospital mortality and non-fatal adverse cardiovascular event (MACE). RESULTS: Mean (SD) age at presentation was 65 (13) years and did not differ among acute coronary syndrome (ACS) types (STEMI= 23%, Non ST Elevation Myocardial Infarction (NSTEMI)= 28%, UA= 49%). ACS is still a disease prevalent in >50 years of age (88%). Dual antiplatelet agents and statin were used >90% cases and coronary angiography was performed in 50% cases. Unstable angina patients has significantly higher number of normal coronaries or non- critical stenosis. Percutaneous coronary intervention rates were significantly higher among STEMI admissions (38% vs 22 % vs 13%, P= 0.003). Unadjusted in-hospital mortality rate was 11%, significantly higher than NSTEMI (5%) and UA (5%). Non-fatal major MACE rate including reinfarction, heart failure or cardiogenic shock was also high in STEMI and NSTEMI patients than in unstable angina patients. CONCLUSION: This study represents contemporary practice of ACS care and provides opportunity to improve care for symptom recognition, treatment options and medical therapy. DOI: http://dx.doi.org/10.3126/jucms.v2i4.12036 Journal of Universal College of Medical Sciences (2014) Vol.02 No.04 Issue 08 Page: 11-14